Orality, gender, and West African Christian spirituality: Exploring women's voices - Fubara-Manuel, Jessie Ini; Fretheim, Sara (Religion Compass, 2023)
This article explores orality in the context of West African Christian women's voices, arguing that their oral expressions highlight their lived faith experiences and function as a significant resource within the study of Christianity in Africa. The article first outlines concepts of orality in relation to gender, spirituality, language, and community engagement. We argue that women's oral contributions are a rich source of insight into West African Christian spirituality but are predominantly marginalised from more formal theological discourse. We further note that orality is not a stepping-stone to formal academic discourse but is instead an equal and important counterpoint requiring attention. These concepts are elucidated through two ethnographic case studies. The first engages Afua Kuma, a non-literate Ghanaian oral artist who adapted chiefly praises for Christologically centred prayers. The second focuses on Hannah (not her real name), a well-educated Nigerian woman living with a disability, for whom singing proved spiritually transformative. We conclude with some of the challenges and benefits of engaging orality.
free